APPLICATION OF QORDH, IJARAH AND WAKALAH BIL UJRAH IN AQAD FINANCING ON FINANCIAL TEHCNOLOGY - Ahmad Zubaidi (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2022)
The development of Sharia Financial Technology raises the question of what contracts are used so that sharia fintech practices are in accordance with sharia provisions. In this interest, DSN MUI has issued Fatwa DSN MUI Number 117/DSN-MUI/II/2018 concerning Information Technology-Based Financing Services Based on Sharia Principles. However, the application of this fatwa also requires other DSN fatwas in order to create a fintech product that can answer the needs of the community but still comply with sharia. One of the products needed by the business world is financing for company receivables due to the provision of work from other parties for which cash payments are not made. One solution is to provide financing by using qordh, ijarah and wakalah bil ujrah contracts. This article will explain how the Qord, Ijarah, and wakalah bil Ujrah contracts are applied to the fintech industry which can be applied to the Islamic finance business, their implementation models, the policies of the Financial Services Authority, and fatwas related to fintech. Berkembangnya Financial Technology Syariah memunculkan pertanyaan akad-akad apa yang digunakan agar praktik fintech syariah sesuai dengan ketentuan syraiah. Dalam kepentingan ini, DSN MUI sudah mengeluarkan Fatwa DSN MUI Nomor 117/DSN-MUI/II/2018 Tentang Layanan Pembiayaan Berbasis Teknologi Informasi Berdasarkan Prinsip Syariah. Namun, demikian dalam pengaplikasian fatwa ini juga membutuhkan fatwa-fatwa DSN yang lain agar tercipta sebuah produk fintech yang dapat menjawab kebutuhan masyarakat tetapi tetap sesuai syariah. Salah satu prodk yang dibutuhkan dunia usaha adalah pembiayaan terhadap piutang perusahaan akibat adanya pemberian kerja dari pihak lain yang tidak dilakukan pembayaran secara kontan. Salah satu solusinya adalah dengan pemberian pembiayaan dengan menggunaan akad qordh, ijarah dan wakalah bil ujrah. Artikel ini akan menjelaskan bagaimana akad Qord, Ijarah, dan wakalah bil Ujrah diterapkan pada Industri fintech dapat diterapkan dalam bisnis keuangan syariah, model-model penerapannya, kebijakan Otoritas Jasa Keuangan, dan Fatwa-fatwa yang berkaitan dengan fintech.